Type 1 Bartter syndrome presenting as primary diabetes insipidus: a rare Case Report with 8-year follow-up - Lu, Huijuan; Liu, Shaojun; Sun, Jia; Mou, Lijun (Frontiers in Genetics, 2025)
Type 1 Bartter syndrome (BS), a rare autosomal recessive salt-losing tubulopathy, classically presents with hyponatremia, hypochloremia, hypokalemic alkalosis, and hyperreninemic hyperaldosteronism. We report a male patient with the atypical presentation of hypernatremia-hyperchloremia, initially misdiagnosed as nephrogenic diabetes insipidus (NDI). Born preterm with antenatal polyhydramnios, he exhibited persistent hypokalemia, polydipsia, and polyuria despite potassium supplementation. Seizures developed at age 9. Genetic testing revealed compound heterozygous SLC12A1 mutations, confirming type 1 BS, while excluding primary NDI (both AVPR2/AQP2 variants were negative). Indomethacin normalized electrolytes and resolved polyuria. Nonadherence to follow-up protocols was observed, including the patient’s unsupervised cessation of indomethacin therapy by the patient at age 14 years. Subsequently, following this unsupervised treatment cessation, he developed focal segmental glomerulosclerosis (FSGS) with renal insufficiency by age 17, alongside intracranial calcifications. This case underscores the fact that hypernatremia-hyperchloremia in BS presenting as secondary inherited nephrogenic diabetes insipidus (siNDI) may mimic primary NDI, and refractory hypokalemia should prompt evaluation for BS. Long-term BS monitoring is critical, given the potential for secondary complications such as FSGS and renal insufficiency, particularly in the context of treatment nonadherence.